Contribution of Philosophical Truth Theory in Strengthening Hadith Science - Fauzi, Irfan (Journal of Islamic Thought and Philosophy, 2024)
In the line of life, humans have knowledge (epistemology) and truth that they believe in, but can this be accounted for? Therefore, these two objects have become mainstream in the branches of philosophy. And so hadith science, the standard of truth of hadith must go through very strict verification. Historically in understanding the truth there are three popular traditional of views; correspondence, coherence, and pragmatics. In the study of hadith science, it is called epistemology of hadith. This theory is very relevant as a form of interconnection of two scientific disciplines (multidisciplinary). This research is a literature review with a descriptive-analysis method. The results of research provide the conclusions that the hadith epistemological framework for testing the validation of a hadith can use these three major views; (1) correspondence (based on empirical-historical data by tracking asbab al-wurud or tarikh al-ruwwah); (2) coherence (based on the principles of mushthalah al-hadith); (3) pragmatics (mashlahah al-ummah). This theory can be a ways of tracing the historical-philosophical validity of hadith so that its truth can be legalized.